Correlation between Pelvic Organ Prolapse Symptoms and Age of Menopause - Rizqy Rahmatyah; Gatut Hardiyanto; Dwi Susanti (Universitas Airlangga, 2017)
Objectives: This study aims to determine the characteristics of patients with POP symptoms in Geriatrics Outpatient Clinic Dr. Soetomo General Hospital.Materials and Methods: This is an analytic observational research with cross-sectional and purposive sampling techniques. The population in this study were patient in Geriatrics Outpatient Clinic Dr. Soetomo General Hospital. Questionnaire was used to collect data and SPSS 21.0 was used for the analysis. 56 patients became subjects in this study. Data were analyzed by chi-square test, Mann-Whitney and Spearman's rho using SPSS 21.0. Results: Data obtained was 13 respondents (23.2%) had symptoms of POP based POPDI-6, with the highest scores of 45.8 (cut-off 75). A significant association was found in the association of menopausal age with symptoms of incomplete voiding (p = 0.036). It is also a risk factor for symptoms of vaginal bulge in patients at Geriatrics Outpatient Clinic Dr. Soetomo General Hospital.